2021
DOI: 10.1101/gr.273300.120
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell tumor immune atlas for precision oncology

Abstract: The tumor immune microenvironment is a main contributor to cancer progression and a promising therapeutic target for oncology. However, immune microenvironments vary profoundly between patients, and biomarkers for prognosis and treatment response lack precision. A comprehensive compendium of tumor immune cells is required to pinpoint predictive cellular states and their spatial localization. We generated a single-cell tumor immune atlas, jointly analyzing published data sets of >500,000 cells from 217 patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 53 publications
3
70
0
Order By: Relevance
“…The three datasets with the lowest correlation coefficient between logOR and logFC (ρ ≤ 0.62) were datasets generated using the Smart-seq protocol (Table 1 ). Across the datasets, we observed an average increase of 1.80 in logOR (median = 1.70, Q 1 = 1.59, Q 3 = 2.10), for every increase in logFC (see Figure 1B for the cancer atlas (2) dataset ( 8 )). The high degree of agreement of detected genes shows that BDA-LR performs on par with the Wilcoxon Rank Sum test, and the strong correlation of the logFC and logOR across all datasets shows that the results can be interpreted in a similar way.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The three datasets with the lowest correlation coefficient between logOR and logFC (ρ ≤ 0.62) were datasets generated using the Smart-seq protocol (Table 1 ). Across the datasets, we observed an average increase of 1.80 in logOR (median = 1.70, Q 1 = 1.59, Q 3 = 2.10), for every increase in logFC (see Figure 1B for the cancer atlas (2) dataset ( 8 )). The high degree of agreement of detected genes shows that BDA-LR performs on par with the Wilcoxon Rank Sum test, and the strong correlation of the logFC and logOR across all datasets shows that the results can be interpreted in a similar way.…”
Section: Resultsmentioning
confidence: 89%
“…For the aging mouse atlases ( 7 ), instead of annotated cell types we retrieved the tissue names. For the cancer atlas ( 8 ), the contrasting cell populations were defined by cell type, so we retrieved the tissue and the cancer-type for each cell. Each dataset was separately pre-processed.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset from the tumor Immune Cell Atlas study [36] was downloaded in the form of an RDS file containing the Seurat object. The cell types in the study were already defined.…”
Section: Analysis Of Single Cell Mrna Sequencing Datamentioning
confidence: 99%
“…For example, using one Smart-Seq2 (deep sequencing depth and high sensitivity) scRNA-seq and 10X Genomics (suitable for detecting large cell populations due to its massive throughputs) scRNA-seq data from CD45 + immune cells, Zhang et al identified LAMP3 + dendritic cells as an important cell type originating from tumors, migrating to hepatic lymph nodes, and shaping the lymphocyte function through antigen-specific priming 8 . The fourth advantage is the ability to build single-cell atlas, such as the tumor immune atlas 9 , in order to provide a comprehensive compendium of immune cells and an inspection of gene expression patterns in different immune cell types.…”
Section: Integrative Analyses Of Scmulti-omics In Immuno-oncologymentioning
confidence: 99%